2015
DOI: 10.1177/1012690215608516
|View full text |Cite
|
Sign up to set email alerts
|

The gap between formalised children’s rights and children’s real lives in sport

Abstract: The purpose of this paper is to use the theoretical standpoint of sociology of childhood to enhance understanding about how children's rights, as outlined by the United Nations Convention on the Rights of the Child, are experienced by child athletes and adult coaches in the context of sport clubs in Sweden. Data were gathered through semi-structured interviews with children and coaches in floorball and equestrian sports during the years 2011 and 2012. The results showed that neither child athletes nor adult co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Few previous English language studies have examined the practices and perceptions of sports coaches in Scandinavia. Eliasson (2015) used a theoretical standpoint of childhood to enhance the understanding about how children's rights, as outlined by the Convention, are experienced by child athletes and six adult coaches in the context of sports clubs in Sweden. The data was gathered through semistructured interviews, and the findings indicated that the participants did not find the Convention meaningful as a policy document, and they did not experience any systematic, deliberate or preventive work with regard to the rights of the child in their sport clubs.…”
Section: Theorising Athletic Talentmentioning
confidence: 99%
See 2 more Smart Citations
“…Few previous English language studies have examined the practices and perceptions of sports coaches in Scandinavia. Eliasson (2015) used a theoretical standpoint of childhood to enhance the understanding about how children's rights, as outlined by the Convention, are experienced by child athletes and six adult coaches in the context of sports clubs in Sweden. The data was gathered through semistructured interviews, and the findings indicated that the participants did not find the Convention meaningful as a policy document, and they did not experience any systematic, deliberate or preventive work with regard to the rights of the child in their sport clubs.…”
Section: Theorising Athletic Talentmentioning
confidence: 99%
“…Knowledge from this study is regarded socially constructed in the interaction between the interviewer and the interviewees through questions and answers, and through transcription, analysis, interpretation and reporting (cf. Eliasson, 2015). Our interview guide was in part based on questions posed by Martindale et al (2007), but was significantly modified to include domainspecific research questions and to suit the Norwegian context.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…6 The Court of Arbitration for Sport (CAS) has been an integral part of this regulatory regime for not only being a supreme arbitral . 5 For details see Esson (2015aEsson ( , 2015b, Stafford et al (2015), and Eliasson (2017). 6 For a detailed historical overview of the system until 2011, see Lembo (2011).…”
Section: Introductionmentioning
confidence: 99%
“…In her recent work, Eliasson (2015) draws on two evident human rights problems that emerge from the sport literature in regard to children's participation: children's rights are violated in sport, and children have a subordinated position relative to adults in the sport context. Violence and abuse of athletic children in the name of their sports is relatively widespread (Eliasson, 2015). This is a broad and complex issue that comprises sexual and emotional abuse from parents and coaches, bullying, and human trafficking of minors in European professional football leagues (Unicef, 2010).…”
Section: Introductionmentioning
confidence: 99%